The Spinozistic Ethics of Bertrand Russell. - Blackwell, Kenneth (Routledge library editions. Russell., 2012)
Bertrand Russell's professional philosophical reputation rests mainly on his mathematical logic and theory of knowledge. In this study, first published in 1985, however, Kenneth Blackwell considers Russell's writings on ethics and metaethics and uncovers the conceptual unity in Russell's normative ethic. He traces that unity to the influence of Spinoza's central ethical concept, the 'intellectual love of God', and then evaluates the ethic which he terms 'impersonal self-enlargement'. The introduction discusses the metaethical background to Russell's ethic and the difficulties inheren.